Dissociation of Quarkonium in a Strong Electric Field; Journal of Experimental and Theoretical Physics; Vol. 126, iss. 5 - Ishkhanyan A. Artur (Nuclei, particles, fields, gravitation, and astrophysics, 2018)
Title screen